2005
DOI: 10.1007/s11284-005-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation analysis in colonies of an endangered rodent, the Cabrera vole (Microtus cabrerae), in southern Portugal

Abstract: The Cabrera vole (Microtus cabrerae) is a threatened rodent endemic in the Iberian Peninsula with a patchy distribution and specific microhabitat requirements. This aim of this study was to document the composition of plant communities in habitats of Cabrera vole colonies in southern Portugal. Differences observed in plant species composition were also compared with vegetation structure, taxonomic and life form groups, species and group diversity, disturbance, topography and soil properties. Vegetation was sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…So if the main aim is to reduce owl roadkills, efforts should focus on the management of road-verge vegetation, reducing the grassland and cover in order to lower its carrying capacity for these groups. However, care must be taken because sometimes road verges act as refuges for small threatened species, as is the case along our surveyed road (Pita et al 2006;Santos et al 2006) for the Cabrera vole (Microtus cabrerae), a rodent species whose IUCN category in Portugal is Vulnerable (Cabral et al 2005). Planting short bushes should decrease the visibility and accessibility of small mammals and insects to the owls (Baudvin et al 1991).…”
Section: Mitigation Measuresmentioning
confidence: 99%
“…So if the main aim is to reduce owl roadkills, efforts should focus on the management of road-verge vegetation, reducing the grassland and cover in order to lower its carrying capacity for these groups. However, care must be taken because sometimes road verges act as refuges for small threatened species, as is the case along our surveyed road (Pita et al 2006;Santos et al 2006) for the Cabrera vole (Microtus cabrerae), a rodent species whose IUCN category in Portugal is Vulnerable (Cabral et al 2005). Planting short bushes should decrease the visibility and accessibility of small mammals and insects to the owls (Baudvin et al 1991).…”
Section: Mitigation Measuresmentioning
confidence: 99%
“…Fedriani et al 2002;Santos et al 2006;Pita et al 2007), both of which are about two times larger for water voles (Román 2003;Pita et al 2006). These preliminary surveys indicated that seven out of 18 sampling sites showed signs of both species, while seven were apparently used by Cabrera voles only and four by water voles only (Fig.…”
Section: Methodsmentioning
confidence: 98%
“…Typically, these habitats include little disturbed and often seasonally flooded tall wet meadows and some adjacent shrubby vegetation able to provide food and protection from predators (e.g. Fedriani et al 2002;Pita et al 2006;Santos et al 2006;Luque-Larena and López 2007;Pita et al 2007;Román 2007). Overall, agricultural development, intensive herbivory by livestock and severe drought episodes are apparently the most important threats across the species' distribution ranges (Fedriani et al 2002;Fernández-Salvador et al 2005a, b;Pita et al 2007;Rigaux and Charruau 2007;Román 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The wood mouse is considered a generalist species that is adapted to agricultural landscapes (Klaa et al 2005;Panzacchi et al 2010) so the observed patterns may not hold for more specialist species, such as the Cabrera vole (Santos et al 2006;Pita et al 2006). The greatest insights into landscape connectivity within the Natura 2000 network will be achieved with an assessment of many species with differing dispersal abilities and ecological requirements (Baguette et al 2013).…”
Section: Figmentioning
confidence: 99%